Integrating Patriotic Spiritualism in Pesantren Education to Cultivate Nationalism - Aip Syarifudin; Ade Aspandi; Nurul Chamidah; Lanlan Muhria; Hagi Al Imam (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2025)
This study examines the integration of patriotic spiritualism into Islamic boarding school education as a model for fostering grassroots nationalism in Indonesia, with a case study at Sabilunnajat Islamic Boarding School in Ciamis. The research aims to understand how spiritual values are reformulated into educational practices that strengthen students’ national identity. Using a qualitative case study approach, data were collected through participatory observation, in-depth interviews with kyais, teachers, students, and community leaders (N = 25), and document analysis of curriculum and activity archives. The data were analyzed through coding, categorization, and thematic interpretation using a phenomenological lens. The findings reveal that Sabilunnajat cultivates patriotism through spiritual habituation, disciplined learning, and the internalization of historical narratives of ulama and santri in Indonesia’s independence struggle. The novelty of this study lies in the concept of patriotic spiritualism as an alternative model of civic education that develops nationalism without military indoctrination. The research concludes that Islamic boarding schools function as grassroots agents of national identity formation by integrating faith-based education with civic values. The study implies that this model can inspire policymakers and educators to strengthen national character through spiritually grounded education.